Confirmation of a Two-Factor Solution to the Questionnaire of Cognitive and Affective Empathy in a French Population of Patients With Schizophrenia Spectrum Disorders - Brunet-Gouet, Eric; Myszkowski, Nils; Ehrminger, Mickael; Urbach, Mathieu; Aouizerate, Bruno; Brunel, Lore; Capdevielle, Delphine; Chereau, Isabelle; Dubertret, Caroline; Dubreucq, Julien; Fond, Guillaume; Lançon, Christophe; et al. (Frontiers in Psychiatry, 2019)
The Questionnaire of Cognitive and Affective Empathy (QCAE) is a tool for self-assessing the cognitive and emotional components of empathy. A study showed that a two-factor model fit the data of patients with schizophrenia, whereas other reports on healthy subjects have suggested a five-factor decomposition. We aimed to replicate the model of Horan et al. in a French population with schizophrenia spectrum disorders (i.e. schizophrenia and schizoaffective disorders) participating to the EVACO study (NCT02901015). In total, 133 patients were assessed with the QCAE, the Positive and Negative Symptom Scale (PANSS), the Personal and Social Performance Scale (PSP), and the Self rating Quality of Life Scale (S-QoL). The two-factor model demonstrated an adequate fit with the data, comparable to that reported by Horan et al. Males scored higher on the Affective sub-score than females. After correction for multiple tests, psychopathology (PANSS) and functioning (PSP) did not correlate significantly with the QCAE subscores. However, Quality of life (S-QoL) correlated positively with the Emotional Contagion sub-score. Thus, the variability of empathetic disposition in schizophrenia may be considered through the cognitive versus affective dichotomy and properly investigated with the QCAE. The results support further investigation of the relationship between QCAE scores and subjective outcome measurements, such as quality of life, and emphasize the importance of cross-cultural comparisons.